NANOTECHNOLOGIES IN BIOMEDICINE - Tursunpulatova Durdona Azamat qizi (American Journal of Biodiversity, 2024)
Nanotechnology has revolutionized various fields, including biomedicine, where it has the potential to transform diagnostics, therapeutics, and drug delivery systems. This article reviews the latest advancements in nanotechnology applications in biomedicine, focusing on nanomaterials, nano-drug delivery systems, and nanodiagnostics. The challenges and future prospects of integrating nanotechnology into clinical practice are also discussed.